Livros didáticos e sociedade digital : os gêneros textuais digitais no contexto escolar - Oliveira, Camila Mota (2015)
The technology promotes transformations in human history, mediates social relationships and leads us to live with an informational deluge daily. As such, it also enters the school, in the use of digital devices and virtual genres made from these technologies, and becomes part of the content of textbooks. The central proposal of the dissertation establishes itself in the analysis and description of the 2011 and 2014 versions of the textbooks of Portuguese Languages collection, in order to sketch an outline of the analytical path in comparison of those versions, in order to examine whether these materials are constituted of proposals aimed to digital text genres in the context of classroom, for the teaching of Portuguese. The guiding theoretical and methodological assumptions of the research is underpinned by in Marcuschi, L. A. (2008) - with proximity to the works of Bronckart (1999); Miller (2012) and Bazerman (2009; 2011) - and Xavier (2009), also followed by studies Levy (1999); Chatfield (2012) and Jenkins (2009). The constitution of the corpus under study took place through the collection of textbooks in both versions of Portuguese Languages collection, one from 2011 and the updated 2014. As a result, we found that, even when dealing with collections of different time points, the follow-up to the 2011 edition of the structure is maintained in the proposals directed to the text genres. The updated version does not bring proposals with clear technological appropriation, however, it refers to digital learning objects still limited way, by only appear in the manuals of teachers. Our contribution lies in the description, analysis and discussion of such notorious restrictions in the educational setting, in relation to language teaching at the time in which we live in a digital society of knowledge, intermediated (and mediated) by technological influence, so we can rethink make pedagogical practice linked to digital technologies (still in basic education) more promising way.